Harga dan Kelengkapan Produk terhadap Keputusan Pembelian pada Toko Sembako Rizkuna Desa Karang Sentosa - Santoso, Teguh; Salam, Munib Alaika (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The purchase decision of consumer is influenced by some factors such as price and product completeness. Facts in Rizkuna Groceries Store are that they set the price higher from the competitor and the product they offer are not complete. Based on those facts, the sales in Rizkuna Groceries Store have decreased. This study was conducted to find out the influence of price and product completeness toward the purchase decision of the customers in the Riskuna Groceries Store in Karang Sentosa Village. The method for this study is quantitative approach along with the customers who ever purchased from the Rizkuna Groceries Store as the respondent. The data collection technique used was a questionnaire, with a total sample of 150 people. Data quality technic was examined with validity and reliability tests. Data analysis test using multiple linear regression. Data analysis test was conducted by partial and simultaneous tests. The results of this study prove that there is a positive and significant effect of price and product completeness on purchasing decisions. Partially, price contributes 24% and product completeness contributes 45.3% to purchasing decisions. Price and product completeness simultaneously affect the purchase decision by 49.6%, and the remaining 50.4% is influenced by other variables